Proqramla idarə olunan şəbəkələrin kibertəhlükəsizlikdə tətbiqi - Abdurahmanov, Arif; Cəlilov, Abdulla; Məmmədov, Sarvan; Zəkiyeva, Nərmin (My University, 2024)
The security of software-defined networks is extremely important in the modern world of information technologies. The analysis of the research shows that methods for protecting these networks from various threats, including cyberattacks, malware, and other types of dangers, require continuous development and improvement. In general, the results of this dissertation can be used to enhance the practical security of software-defined networks and elevate the security landscape in the field of network technologies.
Application of software-defined networks in cybersecurity
Keywords: Proqramla idarə olunan şəbəkələr; Kibertəhlükəsizlik; Software-defined networking; Cybersecurity